Studies on the Rapid and Simple DNA Extraction Method, Antibacterial Activity and Enzyme Activity Involved in Plant Biomass Conversion by Cookeina sulcipes and C. tricholoma (Cup Fungi) - Narumon Tangthirasunun; Supattra Poeaim (Journal of Pure and Applied Microbiology, 2022)
Cookeina sulcipes and C. tricholoma are a cup fungi (Ascomycota) collected in Saraburi, Thailand. The fungi have been isolated, cultured and confirmed as respective species. For morphology, both Cookeina sp. are white mycelium and the growth rate on potato dextrose agar (PDA) result present C. sulcipes is faster than C. tricholoma. The molecular characterization from a rapid and simple DNA extraction method that is modified based on thermolysis method, The DNA extraction is finish in thirty minutes and efficiency to continuous with polymerase chain reaction (PCR) amplification to fungi species level identification. The DNA sequence from internal transcribed spacer (ITS) gene regions by universal primer pairs ITS5/ITS4 is effective to confirm Cookeina species level that C. sulcipes has 616 bp and C. tricholoma has 570 bp. Including, DNA sequence of large subunit (LSU) gene regions by universal primer pairs LROR/LR5 is generate that C. sulcipes has 912 bp and C. tricholoma has 906 bp. The cultures are screened for antibacterial activity by agar plug diffusion method and found that both isolates have been no activity against test strains (Bacillus subtilis, Escherichia coli, Kocuria rhizophila (Micrococcus luteus), Pseudomonas aeruginosa, Staphylococcus aureus and S. epidermidis). In a preliminary screening test of enzymes involved in plant biomass breakdown by agar plate method, both Cookeina sp. show cellulolytic and hemicellulolytic enzymatic activity, and manganese peroxidase (MnP) productivity. In contrast, only C. sulcipes had additional laccase activity. Neither isolate generate pectinolytic and lignin peroxidase (LiP) activities. Thus, Cookeina spp. proved the potentiality to break down lignocelluloses.
Keywords: Plant Pathogens and Fungal Diseases; Enzyme-mediated dye degradation; Mycorrhizal Fungi and Plant Interactions